MOTHERS' FEELINGS ATTRIBUTED TO THE HOSPITALIZATION OF THEIR CHILD - Sarah Vieira Figueiredo; Ilvana Lima Verde Gomes; Viviane Peixoto dos Santos Pennafort; Ana Ruth Macêdo Monteiro; Juliana Vieira Figueiredo (Universidade Federal do Paraná, 2013)
This study aimed to describe the feelings of mothers in experiencing the hospitalization of their child. This descriptive, qualitative research was undertaken in 2012 in a hospital, a center of excellence in Pediatrics, in Fortaleza-Ceará, by means of a semi-structured interview held with mothers accompanying their children, following approval from the Ethics Committee. Based on the analysis of the interviews, two categories were delimited: feelings created in the mother by the falling-ill of her child and strategies for coping with the suffering. The need is evidenced for greater care and interaction on the part of the health professionals with the mothers accompanying children, so as to promote humanized care, involving the mother-child unit.